A point mutation in the Pdia6 gene results in loss of pancreatic β-cell identity causing overt diabetes - Nirav Florian Chhabra; Anna-Lena Amend; Aimée Bastidas-Ponce; Sibylle Sabrautzki; Marta Tarquis-Medina; Stephan Sachs; Marina Rubey; Bettina Lorenz-Depiereux; Annette Feuchtinger; Mostafa Bakhti; Heiko Lickert; Gerhard K.H. Przemeck; et al. (Elsevier, 2021)
Objective: Protein disulfide isomerases (PDIs) are oxidoreductases that are involved in catalyzing the formation and rearrangement of disulfide bonds during protein folding. One of the PDI members is the PDI-associated 6 (PDIA6) protein, which has been shown to play a vital role in β-cell dysfunction and diabetes. However, very little is known about the function of this protein in β-cells in vivo. This study aimed to describe the consequences of a point mutation in Pdia6 on β-cell development and function. Methods: We generated an ENU mouse model carrying a missense mutation (Phe175Ser) in the second thioredoxin domain of the Pdia6 gene. Using biochemical and molecular tools, we determined the effects of the mutation on the β-cell development at embryonic day (E)18.5 and β-cell identity as well as function at postnatal stages. Results: Mice homozygous for the Phe175Ser (F175S) mutation were mildly hyperglycemic at weaning and subsequently became hypoinsulinemic and overtly diabetic at the adult stage. Although no developmental phenotype was detected during embryogenesis, mutant mice displayed reduced insulin-expressing β-cells at P14 and P21 without any changes in the rate of cell death and proliferation. Further analysis revealed an increase in BiP and the PDI family member PDIA4, but without any concomitant apoptosis and cell death. Instead, the expression of prominent markers of β-cell maturation and function, such as Ins2, Mafa, and Slc2a2, along with increased expression of α-cell markers, Mafb, and glucagon was observed in adult mice, suggesting loss of β-cell identity. Conclusions: The results demonstrate that a global Pdia6 mutation renders mice hypoinsulinemic and hyperglycemic. This occurs due to the loss of pancreatic β-cell function and identity, suggesting a critical role of PDIA6 specifically for β-cells.